2021
DOI: 10.1111/jhn.12932
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of nutrition intervention and dietary assessment studies in Khmer populations living in Cambodia

Abstract: Background: This scoping review aims to describe the body of nutrition intervention and dietary assessment research undertaken with Khmer populations in Cambodia, as well as summarise the nutrition knowledge base and highlight priority areas for future research. Methods: Five databases and the grey literature were searched, following PRISMA-ScR guidelines. Studies involving dietary assessment or nutrition interventions published after 1992 were identified using specific search terms and extracted to a customis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…These include the first National Nutrition Strategy 2009–2015, 14 a National Nutrition Program's fast track road map for improving nutrition 2014–2020, 15 the National strategy for food security and nutrition 2019–2023, 2 and the Cambodia Nutrition project with World Bank 16 . Additionally, international researchers have conducted cross‐sectional studies and interventions to inform further policy and programme development 12,13 . Ninety percent of these studies reported being funded by external agencies, many in partnership with the Cambodian government 13 …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…These include the first National Nutrition Strategy 2009–2015, 14 a National Nutrition Program's fast track road map for improving nutrition 2014–2020, 15 the National strategy for food security and nutrition 2019–2023, 2 and the Cambodia Nutrition project with World Bank 16 . Additionally, international researchers have conducted cross‐sectional studies and interventions to inform further policy and programme development 12,13 . Ninety percent of these studies reported being funded by external agencies, many in partnership with the Cambodian government 13 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, international researchers have conducted cross‐sectional studies and interventions to inform further policy and programme development 12,13 . Ninety percent of these studies reported being funded by external agencies, many in partnership with the Cambodian government 13 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations